Neutrophils: Orchestrators of the Malignant Phenotype - Hsu, Brian E.; Shen, Yunyun; Siegel, Peter M. (Frontiers in Immunology, 2020)
Neutrophils are the first leukocytes to be recruited to sites of inflammation, where they execute anti-microbial functions to eliminate infectious agents. These functions include phagocytosis, release of reactive oxygen species and the formation of neutrophil extracellular traps via NETosis. Neutrophils are receiving increasing attention in the context of cancer, where these same neutrophil-associated functions are also important for modulating tumor growth and metastatic progression. Neutrophils are phenotypically heterogeneous and, depending on the context, exert anti- and pro-tumorigenic functions. Increasing evidence also suggests an important role of neutrophils and their involvement in promoting multiple steps of the metastatic cascade. The steps include: 1) local invasion and intravasation of cancer cells into circulation, 2) survival of cancer cells in the bloodstream and extravasation at a distant site, 3) early cancer cell seeding/survival and 4) progressive growth of cancer cells to form macroscopic metastases. Although neutrophil functions designed to eliminate infectious agents can also eliminate tumor cells, their dysregulation can promote tumor growth and enable metastasis at multiple steps along the metastatic cascade. In this review, we will provide an overview of the current advances in neutrophil biology in the context of cancer. We also discuss the emerging field of immunometabolism, in which the rewiring of alternative metabolic pathways within neutrophils can impact their pro-tumorigenic/pro-metastatic functions.